2013
DOI: 10.1007/s13277-013-1203-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of XRCC3 Thr241Met (C18067T, rs861539) and bladder cancer risk: a meta-analysis of 18 research studies

Abstract: The relationship of bladder cancer with the presence of X-ray cross-complementing group 3(XRCC3) genetic polymorphism Thr241Met has been reported with inconsistent results. The objective of this study was to quantitatively evaluate the association between this polymorphism and bladder cancer susceptibility. A comprehensive research was conducted through PubMed, Medline, Embase, and Web of Science databases up to Aug. 20, 2013. Pooled odds ratio and 95 % confidence interval were calculated using a fixed or rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…29 An interaction with smoking may explain some of the heterogeneity observed among prior studies of the X-ray repair complementing defective in chinese hamster 3 (XRCC3) SNP. 30 SLC6A3 variations lead to stress-induced cigarette craving. 31 While data on SNP associations are lacking, growth differentiation factor 15 (GDF15) is being promoted as a biomarker of urothelial cell cancer.…”
Section: Resultsmentioning
confidence: 99%
“…29 An interaction with smoking may explain some of the heterogeneity observed among prior studies of the X-ray repair complementing defective in chinese hamster 3 (XRCC3) SNP. 30 SLC6A3 variations lead to stress-induced cigarette craving. 31 While data on SNP associations are lacking, growth differentiation factor 15 (GDF15) is being promoted as a biomarker of urothelial cell cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Based on a similar hypothesis of influencing radiotoxicity, the association of XRCC3 polymorphisms with cancer risk has also been extensively evaluated. Evidence from meta-analysis supports a positive association between the XRCC3 p.Thr241Met polymorphism and the risk of bladder cancer [ 56 57 ], breast cancer [ 58 59 ], cervical cancer [ 60 61 ] and hepatocellular carcinoma [ 62 63 ]. However, in glioma [ 64 65 ], NSCLC [ 66 67 ], colorectal cancer [ 68 69 ] and gastric cancer [ 70 71 ] patients, the associations were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Although the functional relevance of the XRCC3 Thr241Met variation is unknown, some studies have reported that this polymorphism is associated with increased risk of breast cancer [ 20 ]. A meta-analysis has revealed that the XRCC3 gene rs861539 polymorphism also increases the risk of developing hepatocellular carcinoma, as well as head and neck, bladder, and breast cancer [ 11 , 32 , 33 , 60 62 ]. However, this polymorphism has also been shown to have a weak association with the risk of breast cancer as well as lung cancer [ 63 , 64 ] and no connection with the development of ovarian, cervical, or colorectal cancer or renal cell carcinoma [ 9 , 65 67 ].…”
Section: Discussionmentioning
confidence: 99%